MORPHOLOGICAL-SYNTACTIC FORMATIONS IN ENGLISH AND UZBEK TELEVISION DISCOURSE: A COMPARATIVE LINGUISTIC ANALYSIS (American Journal of Pedagogical and Educational Research, 2026)
This study presents a comprehensive comparative analysis of morphological-syntactic formations in English and Uzbek television discourse, focusing on their structural, semantic, and functional characteristics. Television discourse, as a dynamic communicative domain, reflects rapid linguistic changes influenced by globalization and technological development. The research examines five major formation types—compounding, affixation, syntactic constructions, discourse formulas, and abbreviations—based on a dataset of 30 representative lexical units. The findings demonstrate that Uzbek exhibits a high degree of productivity in derivational morphology due to its agglutinative nature, whereas English shows greater flexibility through conversion and compounding. Despite typological differences, both languages share similar syntactic patterns, particularly in attributive constructions. The study contributes to the fields of media linguistics and comparative linguistics by systematizing television-related lexical units within lexical-semantic and structural-semantic frameworks.